Dattātreya : the immortal guru, yogin, and avatāra : a study of the tranformative and inclusive character of a multi-faceted Hindo deity - Rigopoulos, Antonio, 1962- (SUNY series in religious studies., 1998)
The book presents the multi-faceted Hindu deity Dattatreya from his Puranic emergence up to modern times. Devotion to Dattatreya cuts through all social and religious strata of Indian society: among his adepts we find yogis, Brahmans, faqirs, Devi worshippers, untouchables, thieves, and prostitutes. This book explores all primary religious dimensions: myth, doctrine, ritual, philosophy, mysticism, and iconography. The comprehensive result offers a rich fresco of Hindu religion as well as an understanding of Marathi integrative sprituality: precisely this complexity of themes constitutes Dattatreya's uniqueness. -- Provided by publisher.